Demographic translation: From period to cohort perspective and back - Nico Keilman (University of Oslo, Department of Economics, 2000)
When successive birth cohorts of women get their children at progressively lower ages, births that would have occurred during a certain period without changes in the timing, are now “squeezed” into a shorter period. This pushes period fertility up, and the period Total Fertility Rate (TFR) will be inflated, compared to the TFR that would have occurred without changes in the timing. In general, even when the number of children per woman is constant over successive birth cohorts, period fertility levels may vary – they are inflated in years in which childbearing is accelerated, and deflated when women postpone childbearing. Thus period fertility cannot be used as a reliable indicator for the level of cohort fertility: period fertility may be “distorted” in times of tempo changes in cohort fertility. At the same time cohort fertility cannot be fully understood without studying periods. These qualitative links between period and cohort fertility are straightforward. But the detailed interplay between period and cohort fertility, both its quantum (level) and tempo (timing) aspects, can be formalized mathematically. The resulting expressions constitute the core of what has become known as the theory of demographic translation, a term coined by Norman Ryder. This chapter gives a brief general overview of demographic translation theory. It integrates Ryder's findings from the 1960s that he applied to age specific fertility, with more recent insights, which can be used for analysing other demographic processes, such as childlessness, first marriage, and divorce.
Keywords: 330; Fruchtbarkeit; Theorie; Kohortenanalyse